2021
DOI: 10.1093/ageing/afab042
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between frailty and delirium: insights from the 2017 Delirium Day study

Abstract: Background although frailty and delirium are among the most frequent and burdensome geriatric syndromes, little is known about their association and impact on short-term mortality. Objective to examine, in hospitalized older persons, whether frailty is associated with delirium, and whether these two conditions, alone or in combination, affect these patients’ 30-day survival. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Frailty is a geriatric condition characterized by increased vulnerability for adverse events. Many studies have demonstrated that frailty increases the risk of delirium underscoring the need for early screening of frailty in hospitalized patients [ 25 27 ]. The reason for this increased susceptibility is likely related to the pathophysiological link between frailty and delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty is a geriatric condition characterized by increased vulnerability for adverse events. Many studies have demonstrated that frailty increases the risk of delirium underscoring the need for early screening of frailty in hospitalized patients [ 25 27 ]. The reason for this increased susceptibility is likely related to the pathophysiological link between frailty and delirium.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of patients (≥ 70 years) admitted to acute medical care, the overall impact of delirium on admission tends to be greater at lower levels of frailty (P = 0.07) [15]. A study of 2,065 patients aged 65 years or older hospitalized in 118 acute medical wards and 46 rehabilitation units in Italy found that there was no interaction between delirium and frailty on 30-day mortality (P = 0.477) [32]. The discrepant findings between studies may relate in part to variations in study populations, sample size, and tools for the assessment of frailty and delirium [6,33].…”
Section: Discussionmentioning
confidence: 98%
“…Eeles et al 45 ) assessed the impact of frailty on mortality among older inpatients who had delirium in a single-center study and reported that frail patients had greater long-term mortality among those with delirium compared with that among those without frailty—median survival of 88 days (95% CI, 5–171) for frail patients vs. 359 days (95% CI, 118–600) for fit patients. However, Mazzola et al 46 ) reported that delirium alone was not associated with mortality after adjusting for frailty, supporting the role of frailty as a confounder, increasing the vulnerability to stressors that lead to death. Dani et al 47 ) conducted a survival analysis to identify the impact of delirium on frailty in hospitalized older adults; interestingly, they reported an inverse gradient of association, with a stronger association observed in the fitter group and a higher hazard ratio for delirium in patients with a lower frailty index.…”
Section: Role Of the Interaction Between Frailty And Delirium In Clinical Outcomesmentioning
confidence: 98%
“…45 However, Mazzola et al reported that delirium alone did not show association with mortality after adjusting frailty, supporting the statement that frailty plays a role as a confounder, increasing the vulnerability to stressors that lead to death. 46 More interestingly, Dani et al conducted a survival analysis to identify the impact of delirium on frailty for hospitalized older adults and reported an inverse gradient of association, that stronger association were observed in the fitter group -patients with lower frailty index had a higher hazard ratio from delirium. 47 Besides the mortality as a clinical outcome, a single-center study by Ogawa et al assessed the impact of post-operative frailty on major adverse cardiac events after cardiac surgery.…”
Section: The Interaction Of Frailty and Delirium On Clinical Outcomesmentioning
confidence: 99%